Kebijakan Pendidikan Islam: Hibridasi Lembaga Pendidikan Tinggi - Andi Wahyono (Jurnal Pendidikan Islam, 2014)
This paper is going to discuss and to provide solutions for the problems of dualism policy in the Islamic higher education institution. The effort to integrate religious education and general education has not reached a satisfactory result. Several concepts have been offered, but they still leave the problems of dualism policy in the Islamic higher education institution. Therefore, I offer the concept of hybridization of higher educations. This endeavor is very urgent to be done because there is a tendency of Islamic higher education institutions and general higher education institutions to be more apart, although there are the offers of the concept of science Islamization, Islam as Science, or the integration and interconnection of science.